Balance and mobility relationships in older adults: A representative population-based cross-sectional study in Madeira, Portugal. (January 2019) - Gouveia, Élvio R.; Gouveia, Bruna R.; Ihle, Andreas; Kliegel, Matthias; Marques, Adilson; Freitas, Duarte L.
Highlights: Balance and mobility were negatively associated with age and BMI. Men presented better balance and mobility performances than women. Balance and mobility were positively related to physical activity. Functional fitness explained the largest part of variance in balance and mobility. Aerobic endurance had the strongest contribution to explain balance and mobility. Abstract: Background: Balance and mobility impairments are important modifiable risk factors associated with falls in older people. Purpose: To investigate how different functional fitness components relate to balance and mobility, after controlling for age, sex, body mass index (BMI), and different physical activity (PA) domains. Methods: This representative cross-sectional study included 802 individuals, 401 males and 401 females (69.8 ± 5.6 years) from Madeira, Portugal. The Fullerton Advance Balance (FAB) scale was used to assess balance. Mobility in terms of gait velocity, cadence, stride length, and gait stability ratio (GSR) were assessed using the 50-foot Walk test. PA was assessed through a face-to-face interview using the Baecke questionnaire, and functional fitness was assessed with Senior Fitness tests (strength, flexibility, and aerobic endurance). Results: Balance and mobility were negatively associated with age and BMI, and positively related to PA and functional fitness. Moreover, male presented better performance in balance and mobility. Hierarchical multiple regression analyses showed that functional fitness explained the highest amount of variance in balance and all mobility parameters (over and above age, sex, BMI, and PA). Specifically, entering functional fitness components significantly increased explained variance in FAB (+19%), gait velocity (+25%), cadence (+15%), stride length (+9%), and GSR (+ 31%). In these models, aerobic endurance consistently had the strongest contribution. Conclusion: Strength, flexibility, and especially aerobic endurance, over and above non-modifiable variables like age and sex, are crucial for maintaining or improving balance and mobility and, thereby, prevent falls in older people.